Design of remnant pillar in mechanized depillaring using continuous miner - Chawla S.; Jaiswal A.; Shrivastva B.K. (My University, 2025)
Ribs and snooks are the critical natural support at the goaf edge in the mechanized depillaring operation of the bord and pillar mining system. The pillar extraction has been carried out by taking the slices and leaving ribs and snooks during the depillaring operation. Remnants are the remaining portion of the extracted pillar. The depillaring operation leads to an unsupported roof, and the immediate unsupported roof imposes its weight on the pillar (remnant) under extraction. The remnant’s purpose is to provide a necessary reaction to the overhang to restrict roof failure until the pillar’s final slice. The remnant’s stability during depillaring operation has been accessed in the study using three-dimensional numerical simulations. A scheme has also been proposed in the study to evaluate the factor of safety (FOS*) of the remnant pillar in the residual phase at different stages of slicing operation. A case of an Indian coal mine using the fish-bone method has been chosen for the study. A typical depillaring stage has been selected for the extraction of the pillar using the fish-bone method. The numerical simulation of the considered panel provides the vertical stress and yielding profile on the pillars at different stages of depillaring. The simulation results show the influence zone up to one pillar from the goaf edge. The immediate intact pillar shows considerable yielding of about 60% of the pillar area. The remnants have completely yielded during the slicing operation but provide a reaction to the immediate strata. The remnant should provide the reaction to the immediate roof till taking the final slice from the pillar. The remnant’s FOS* is calculated by taking the ratio of reaction offered by the remnant (numerical simulations) and the weight of the overhang (estimation). The area’s borehole section shows two layers of medium to coarse-grained sandstone as an immediate stratum. The weight of the immediate strata has been estimated in the study considering the immediate strata’s thickness. Two different scenarios of immediate strata thickness (i.e., 4.75 m and 9 m) have been considered in the study to evaluate the remnant’s FOS at different depillaring stages. © 2021, Books and Journals Private Ltd.. All rights reserved.